Pengaruh Customer Review dan Price terhadap Keputusan Pembelian Furniture KM Top pada TikTok Shop - Vincent Susanto; Rizky Chandra Fahlevy; Elke Alexandrina (BJRM (Bongaya Journal of Research in Management), 2026)
This study aims to examine the effect of customer reviews and price on purchasing decisions of KM Top furniture products on the TikTok Shop platform. The rapid development of social commerce has changed consumer behavior, particularly in evaluating product information and pricing before making purchasing decisions. Customer reviews serve as a source of information that can reduce uncertainty in online shopping, while price acts as a rational consideration for consumers in selecting products among various alternatives. This research employs a quantitative approach with a causal associative design. The population consists of consumers who have purchased KM Top furniture products through TikTok Shop. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression. The results indicate that customer reviews have a positive and significant effect on purchasing decisions. Price also has a positive and significant influence on purchasing decisions. Simultaneously, customer reviews and price significantly affect purchasing decisions. These findings suggest that both review quality and price perception are important factors influencing consumer purchasing decisions in social commerce platforms. This study contributes to consumer behavior research in the context of social commerce and provides practical insights for furniture businesses operating on TikTok Shop.